2013
DOI: 10.2134/jeq2012.0203
|View full text |Cite
|
Sign up to set email alerts
|

Soil Nutrients, Bacteria Populations, and Veterinary Pharmaceuticals across a Backgrounding Beef Feedlot

Abstract: Beef cattle backgrounding operations that grow out weaned calves for feedlot finishing contain several environmentally significant constituents. A better understanding of these constituents and their environmental distribution will aid in the development of effective management guidelines for sustainable beef production. This research investigated soil nutrients, bacterial, and veterinary pharmaceutical concentrations across a small backgrounding beef feedlot on a karst landscape. Results indicated that all co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Samples were taken at a soil depth of 0 to 15 cm by combining 15 soil samples from each plot. Composite samples were used to determine soil pH, dry weight, and nutrient analysis as previously described (Netthisinghe et al, 2013). Poultry litter consisting of a mixture of excreta, sawdust bedding, wasted feed, and feathers was obtained fresh from a broiler ( Gallus gallus domesticus ) house located in western Kentucky.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were taken at a soil depth of 0 to 15 cm by combining 15 soil samples from each plot. Composite samples were used to determine soil pH, dry weight, and nutrient analysis as previously described (Netthisinghe et al, 2013). Poultry litter consisting of a mixture of excreta, sawdust bedding, wasted feed, and feathers was obtained fresh from a broiler ( Gallus gallus domesticus ) house located in western Kentucky.…”
Section: Methodsmentioning
confidence: 99%
“…This research was conducted at the Western Kentucky University Agricultural Research and Education Complex Site, Bowling Green, KY (36.92831° N, 86.46839° W). Based on the preliminary information of the site (Netthisinghe et al, 2013), this study focused on the feeder (FD) and grazing (GR) areas of the backgrounding feedlot. The FD area of the feedlot measured 2400 m 2 , and the GR area covered 21,900 m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Both large and small intensive animal production sites have reported greater soil nutrient levels ( Jongbloed and Lenis, 1998) and microbial populations (Gerba and Smith, 2005). In a recent study, Netthisinghe et al (2013) identified feeder and nearby grazing locations within a small backgrounding beef feedlot containing elevated soil nutrients and high microbial populations. Soil nutrients in excess of plant demand can accelerate emissions, leaching, and surface runoff nutrient losses (Franzluebbers et al, 2000).…”
Section: Management Practices Affect Soil Nutrients and Bacterial Popmentioning
confidence: 99%
“…Of the ingested minerals and antimicrobial compounds, significant amounts are excreted in manure (Levy, 1992; ASAE, 2005; Kumar et al, 2005). As a result, areas receiving heavy manure loads can have elevated soil nutrient levels (Dantzman et al, 1983) and residual antimicrobial concentrations (Netthisinghe et al, 2013). Of manure‐derived soil nutrients, P is identified as the major nutrient that affects water quality (Sharpley et al, 1994).…”
mentioning
confidence: 99%
“…Due to partial absorbance in the ruminant body, a significant proportion of monensin can pass through to the environment. Netthisinghe et al (2013) reported 86.9 ng monensin g −1 in the feeder and adjacent soils on a semi‐intensive small beef backgrounding site. Evidence suggests that antimicrobial compound residues in soils can impose selective pressure on the resident flora, resulting in increases in bacteria carrying antibiotic resistance genes (ARGs) and increasing the potential for ARGs to be horizontally transferred between soil bacterial community members (Xiong et al, 2015).…”
mentioning
confidence: 99%